The New Perspective challenge to Luther - Eriksson, Bart (HTS teologiese studies, 2019)
New Perspective scholars challenge Protestant interpretations of Paul. It used to be the case, they state, that Protestants assumed that Paul was to Judaism as Luther was to Medieval Catholicism. Both men supposedly reacted against legalistic religions and championed grace-based faiths. However, in 1977, E.P. Sanders wrote Paul and Palestinian Judaism, arguing that Judaism is not a legalistic but a grace-based faith. Assuming that Sanders is correct, New Perspectivists claim that Paul’s and Luther’s theologies and experiences were thus not parallel. Hence, Luther misunderstood Paul. Additionally, New Perspectivists challenge Protestant understandings of ‘justification’. In New Perspective thought, Paul uses the term ‘justification’ primarily to describe how people, particularly Gentiles, join the church Christians without following Jewish ritual laws. ‘Justification’, then, does not describe how people ‘stay in’ the covenant and receive salvation, as Protestants think. However, this article maintains that while New Perspectivists have some knowledge of Paul and Judaism, they are much less knowledgeable regarding Luther, Medieval Catholicism and Luther’s reaction to it. Greater scrutiny of these latter areas reveals large difficulties with New Perspective arguments. In addition, a review of relevant passages from Paul’s letters demonstrates that Protestants have not misunderstood Paul’s use of the term ‘justification’. Many Pauline passages show that when Paul discusses justification he is also thinking about ‘staying in’, not just ‘getting in’ the covenant.